War commandant of Lithuanian National Labour Protection Battalion of Kaunas in 1941 - Knezys, Stasys (Genocidas ir rezistencija, 2000)
The Lithuanian National Labour Protection Battalion, the formation of which started in Kaunas on 28 June 1941, when the German–Soviet front line had already swept eastwards through Lithuania, is one of the more vivid and dramatic pages in the history of the Lithuanian army. It is the history of the Lithuanian army, because the Soviet occupiers had disbanded the army by way of incorporating it into the red army and naming it territorial riflemen unit No. 29 (later – TRU No. 29), while a significant part of Lithuanian fighters, officers in particular, were dismissed from the service. However, the incorporation only destroyed the structure and appropriated the weapons and property of the army. The spirit of independence nurtured and cherished in pre–war Lithuania persisted. The TDA (i.e., national labour service) Battalion is an expression of hope for the re–establishment of the Lithuanian army.